I'DAD BARNAMAJ AL-FORTOPOLIO AL-ELEKTRONI WA TASHMIMUHU FI TA'ALUM AL-LUGHAH AL-'ARABIYAH - Mohd Firdaus bin Yahaya; Mohd Feham Md. Ghalib; Mohd Shahrizal Nasir; Mohd Fauzi Abdul Hamid (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2016)
This research was aimed at examining the use of e-portfolio in learning process for Arabic as a foreign language in Malaysia and explaining the steps in using the e-portfolio designed as a teaching media in modern era. this research was also intended to know the extent to which the interests of Arabic language students on the use of e-portfolio at International Islamic University Selangor Malaysia. The questionnaire was used for the instrument given to 30 students as the samples. The value of cronbach alpha reliability coefficient was (0.913) for the statements set in the questionnaire. The research found some findings, yet the most important one was that students’ interest on using e-portfolio was high valued as (4.39). This research concluded that e-portfolio is a help for students’ learning process on Arabic language either for intermediate or beginner level.DOI: 10.15408/a.v3i2.3579